THE INTEREST OF THE INVESTOR IN ACCOUNTING PRINCIPLES. - Morrison, Paul L. (The Accounting Review, 1937)
Financial statements are important tools of the intelligent investor. The investor wishes that more attention be given to substance rather than form in financial statements and in reports to governmental agencies such as the U.S. Securities and Exchange Commission. Accountants should recognize that investors are the principal group interested in published financial statements, and that more attention should be given to completeness rather than technical accuracy, particularly in the income statement. Public accountants are influenced to some extent by the managements of businesses which employ them. Resulting financial statements, then, are compromises to a greater or less degree. A substantial part of corporate capital is supplied by investing stockholders and bondholders. Such investors exercise practically no control over the affairs of the companies involved. If results are not satisfactory to them their alternative is to sell. If the results appear to be attractive their alternative is to buy more. Controlling stockholders dominate the management and are in position to influence management policies in order to protect or improve their commitments.